2011
DOI: 10.1111/j.1365-2052.2011.02287.x
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differential gene expression in sensitive and resistant pig toEscherichia coliF18

Abstract: In this study, Agilent two-colour microarray-based gene expression profiling was used to detect differential gene expression in duodenal tissues collected from eight full-sib pairs of Sutai pigs differing in adhesion phenotype (sensitivity and resistance to Escherichia coli F18). Using a two-fold change minimum threshold, we found 18 genes that were differentially expressed (10 up-regulated and eight down-regulated) between the sensitive and resistant animal groups. Our gene ontology analysis revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Based on the paired full-sib individuals that were selected from an established resource of Sutai pigs (Duroc x Meishan) that were characterized as resistant or sensitive to E. coli F18, our research team identified the expression profiles of some genes, including TAP1, in duodenum. The results showed that TAP1 played a vital role in resisting E. coli F18 infection (Bao et al, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Based on the paired full-sib individuals that were selected from an established resource of Sutai pigs (Duroc x Meishan) that were characterized as resistant or sensitive to E. coli F18, our research team identified the expression profiles of some genes, including TAP1, in duodenum. The results showed that TAP1 played a vital role in resisting E. coli F18 infection (Bao et al, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Mammalian TLRs constitute a large family of transmembrane receptors, of which TLR4 has received the most attention and has been found to induce the production of inflammatory factors and cytokines during anti-infection and immunity processes (Takeda and Akira 2005, Zacharowski et al 2006. We previously used Agilent two-color microarray-based gene expression profiling to investigate differential gene expression, and found that the TLR4 signaling pathway may regulate resistance to E. coli F18 in weaned piglets (Bao et al 2012). Meishan pigs, a popular Chinese local breed, were infected with E. coli F18 and examination of intestinal tissue, bacterial counts and binding assays revealed two distinct resistant and sensitive phenotypes (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted in 3 E. coli F18-resistant piglets and 3 E. coli F18-susceptible piglets (Bao et al, 2012). All experiments were conducted in the Animal Hospital of Yangzhou University according to the regulations of the Administration of Affairs Concerning Experimental Animals (Ministry of Science and Technology, China, revised in June 2012) and approved by experimental animal using permit with No.…”
Section: Differential Expression Of Porcine Bpi Gene In E Coli F18-rmentioning
confidence: 99%